The Influence of Content Creation, Content Sharing, and Connecting on Customer Decisions through Community Building for the IndiHome Product - Miftachul Kamal, Mohamad; Khodir Djaelani, Abdul; Malavia Madani, Ronny (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the influence of Content Creation, Content Sharing, and Connecting on Customer Decisions through Community Building for the IndiHome Telkom product (Case Study of Witel Telkom Pasuruan, East Java). This research uses a quantitative approach. The sample size is 91 based on Cooper and Emory. The analysis model uses Moderated Regression Analysis (MRA) and Structural Equation Model (SEM) based on Partial Least Square (PLS) with the help of SmartPLS version 3.0. The results showed that the content creation variable does not affect customer decisions. Content sharing and connecting variables do affect customer decisions. Community building influences customer decisions. However, community building does not mediate the relationship between content creation and customer decisions. On the other hand, community building does mediate the relationship between content sharing and customer decisions. Lastly, community building does not mediate the relationship between connecting and customer decisions